Salivary Gland Dysplasia in Fgf10 Heterozygous Mice: A New Mouse Model of Xerostomia - May, A.J.; Chatzeli, L.; Proctor, G.B.; Tucker, A.S. (Current Molecular Medicine, 2015)
Xerostomia, or chronic dry mouth, is a common syndrome caused by a lack of saliva that can lead to severe eating difficulties, dental caries and oral candida infections. The prevalence of xerostomia increases with age and affects approximately 30% of people aged 65 or older. Given the large numbers of sufferers, and the potential increase in incidence given our aging population, it is important to understand the complex mechanisms that drive hyposalivation and the consequences for the dentition and oral mucosa. From this study we propose the Fgf10 +/- mouse as a model to investigate xerostomia. By following embryonic salivary gland development, in vivo and in vitro, we show that a reduction in Fgf10 causes a delay in branching of salivary glands. This leads to hypoplasia of the glands, a phenotype that is not rescued postnatally or by adulthood in both male and female Fgf10 +/- mice. Histological analysis of the glands showed no obvious defect in cellular differentiation or acini/ductal arrangements, however there was a significant reduction in their size and weight. Analysis of saliva secretion showed that hypoplasia of the glands led to a significant reduction in saliva production in Fgf10 +/- adults, giving rise to a reduced saliva pellicle in the oral cavity of these mice. Mature mice were shown to drink more and in many cases had severe tooth wear. The Fgf10 +/- mouse is therefore a useful model to explore the causes and effects of xerostomia.
Keywords: salivary gland dysfunction